En los accidentes de tránsito se debe considerar el auxilio y la ayuda inmediata proporcionada a la víctima, como atenuante trascendental para proteger el derecho a la vida de la víctima - Benítez Rodríguez, Silvana Marisol (2015)
This work is framed within the guidelines established in the National University of Loja, the issue under discussion is "IN TRAFFIC ACCIDENTS MUST CONSIDER THE IMMEDIATE RELIEF AND VICTIM ASSISTANCE PROVIDED AS EXTENUATING TRANSCENDENTAL RIGHT TO PROTECT. a LIFE oF VICTIM "to whose study we consider the general objective : " Make a legal , critical and doctrinal study of the Law of Land Transport , traffic and Road Safety , regarding traffic violations and the circumstances in committed , as well as other standards that relate to this , in order to find the basis of the problem and give a solution. " In order to achieve this goal, we made use of various scientific methods used in the research process, such as: Inductive , deductive , analytical, statistical, etc., and also apply a survey of 30 lawyers , of who got valuable results and the fact that most respondents said it is important to add in paragraph a ) , first indent , timely and spontaneous repair of damage caused , held up before pleading installed trial hearing . The research concludes with the presentation of the proposal to amend the Organic Act of Terrestrial Transport Traffic and Road Safety, this being the result of the analysis of all the data obtained during the research process.